Reform of the quality management system of higher education of the Kyrgyz Republic (within the framework of «Tempus») (Journal of Educational Sciences, 2016)
The article deals analysis of relevant procedures of quality rating of education in universities of Kyrgyzstan. It describes the role of the educational projects of the European Commission Tempus program to reform the system of management quality of high school in Kyrgyzstan, given the newly adopted amendments to the law on the formation of an independent accreditation of educational institutions. Also, this article explains the provisions of the Bologna process and the principles of the Bologna Declaration, in particular,it is determined that: 1) one of the Bologna Declaration is to promote European cooperation in quality assurance with a view to developing comparable criteria and evaluation methodology. 2) describe and analyze the ways to implement the principles of the Bologna process as a whole in Kyrgyzstan.3) are analyzed, solutions to problems in the light of the harmonization of quality control of education, and were introduced fundamental changes in the legislation, such as the transition from the certification procedure for the procedure an independent accreditation.
Keywords: Bologna process; the law of education in Kyrgyz Republic; higher professional education; institution of educational attestation and license; higher professional educational reform; independent accreditation of educational institution national institutions